Preliminary ultrasonographic studies on an electronic system for focusing an ultrasonic beam - WASZCZUK, Tomasz; ŁYPACEWICZ, Grażyna; SOMER, Jan (Archives of Acoustics, 1989)
In conventional mechanical contact scanners the lateral resolution is inferior to the axial one. Improving the lateral resolution over a wide range of depth requires the use of variable focusing system. We choose the phase annular array system which may be used in obstetrics and gynaecology.Measurements of the ultrasonic beam were carried out. Visualisations two different phantoms AIUM-100 and RMI-402 were performed during work: a typical B-scanner, and the annular array system. The results indicate a considerable increase in the lateral resolution when works the annular array system.